Правовий статус єврейського населення та антиєврейська політика Російського самодержавства в Україні ( 1880 - 1907рр. ) - Кальян, О.С.; Кальян, О.С.; Нookah, О. (My University, 2011)
The article deals with urgent legal matters of legal status of jewish popula- tion and antijewish policy of Russian autocracy in Ukraine (1880 – 1907). The author of the article proves that Jews were one of the biggest ethnic groups in Ukraine, and due to speciﬁ c conditions of settling and their occupations Jews considerably deﬁ ned the character and the structure of economical and law processes in Ukraine and also helped considerable improvements in the sphere of law policing social relations in Ukraine those period.
Кальян О.С. Правовий статус єврейського населення та антиєврейська політика Російського самодержавства в Україні ( 1880 - 1907рр. ) / О.С. Кальян // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 12-18 . С. 322 - 331.
Keywords: Єврейське населення; Антиєврейська політика; Правовий статус єврейського населення; Етнічні групи; Этнические группы; Правовой статус еврейского народа; Антиеврейская политика; Еврейское население; The Jewish population; The anti-Jewish policy; The legal status of the Jewish people; ethnic groups